Study of feasibility of daycare surgery in tertiary health center - J.B. Hedawoo; Amrin Sheikh (Al Ameen Medical College, 2016)
Aim: To study the feasibility of daycare surgery in a tertiary care center. Background: Day care surgery is advantageous to patient in terms of early recovery less hospital stay, less rate of complications. Now a-days number of day care surgeries has increased and nearly 50 percent surgeries in western countries are done on daycare basis. Methods: This is Hospital Based observational study carried out in Department of Surgery in tertiary care center over the period from August 2013 to November 2015. Results: 300 patients selected for day care surgery in our institute. Among the 300 patients, males were 284(94.7%), females were 16 (5.3%). All patients discharge within 23 hr of surgery and follow up on 3rd day, 7th day, 1 month and 6 month. Age ranged from 1 to 80 years and mean age was 32.68+/-21.94 years. The procedures performed included surgery for inguinal hernia in 103(34.3%), appendicitis in 49 (16.3%), hydrocele in 45(15%), surgery for congenital hernia in 46(15.3%) and phimosis in 40(13.3%) patients. On evaluation of complications assessed at follow-up after 3 days, 8 patients had infection, on 7th day 1 patient had infection and 1 had reinfection, none of the patients required re-admission. Conclusions: Our study showed that daycare surgery is feasible in tertiary health center and advantageous to patient with low rates of complications.